An heiress to austin : Stanley cavell, Henry James and the Hollywood melodrama of the unknown woman - Jukić, Tatjana (2008)
When addressing "the peculiar distribution of power between arts" (here, between film and literature)— at that point in Contesting Tears where he aims to posit film and psychoanalysis as technologies where philosophy is inherited— Stanley Cavell uses Henry James as a figure that anticipates this positionality from within literature. James seems to mark this spectral positionality throughout Cavell, most conspicuously perhaps in a chapter title like "Henry James Returns to America and to Shakespeare" (Philosophy the Day After Tomorrow)— the chapter concluding symptomatically with a reference to Derrida's Specters of Marx. One could almost argue that Henry James is to Cavell what Hamlet is to Marx and then to Derrida, in Specters of Marx: both the ghost of literature and the literature of ghosts, where this "both" opens as a positionality to philosophy's own (mnemo)technology. In order to approach Henry James from this perspective, and see what Cavell in turn does to James in the reemergence of James within philosophy, I will take up Washington Square as a kind of parable. On the one hand, in James's oeuvre this novel emerges as a ghost confronting what James acknowledges as legacy and anticipation of literature ; on the other, this novel was ultimately inherited as film (William Wyler's The Heiress, 1949), specifically where film exposes its co-genealogy with psychoanalysis— the juncture towards philosophy that Cavell in Contesting Tears analyzes as the Hollywood melodrama of the unknown woman.